Association between 24-hour blood pressure variability and mortality in acute ischemic stroke patients admitted in intensive care units: a MIMIC-IV study - Zhen Yuan; Yunqing Zeng; Zhizhen Shi; Aoli Chen; Yangbo Hou; Guoyi Li; Jiwei Cheng (Blood Pressure)
Introduction Acute ischaemic stroke (AIS) patients in the intensive care unit (ICU) face high mortality. This study examined the association between systolic blood pressure variability (SBPV), specifically average real variability (SBP-ARV), and short-term mortality in critically ill AIS patients.Methods We conducted a retrospective cohort study using the MIMIC-IV database. The primary outcomes were 28-day and 90-day all-cause mortality. Cox regression, Kaplan-Meier curves, restricted cubic spline (RCS) models, and subgroup analyses were used to assess associations.Results A total of 861 AIS patients were included. The 28-day and 90-day mortality rates were 20.9% and 23.3%, respectively. Higher SBP-ARV was independently associated with increased mortality. Compared with the lowest tertile, the highest tertile of SBP-ARV had significantly increased 28-day mortality (HR: 1.53; 95% CI: 1.03–2.27; p = 0.035). SBP-ARV as a continuous variable was also significantly associated with 28-day and 90-day mortality. RCS analysis showed that mortality risk increased when SBP-ARV exceeded 11.63.Conclusion Our findings suggest that elevated systolic blood pressure variability, particularly higher SBP-ARV within the first 24 h of ICU admission, is significantly associated with increased 28-day and 90-day mortality in AIS patients. SBP-ARV may serve as a valuable prognostic marker for risk stratification and early clinical intervention in critically ill stroke patients.